Zinc‐Ion Batteries: Electronic Structure Regulation of Layered Vanadium Oxide via Interlayer Doping Strategy toward Superior High‐Rate and Low‐Temperature Zinc‐Ion Batteries (Adv. Funct. Mater. 6/2020). (5th February 2020) - Geng, Hongbo; Cheng, Min; Wang, Bo; Yang, Yang; Zhang, Yufei; Li, Cheng Chao
Abstract : In article number 1907684, Cheng Chao Li and co‐workers demonstrate that interlayer Mn 2+ ions–doped layered vanadium oxide composites with a narrowed direct bandgap manifest fast electrons/ions transport kinetics and good structural stability. When evaluated as cathodes for zinc‐ion batteries, the as‐prepared electrode delivers superior zinc‐ion storage properties in terms of high specific capacity, stable cycling capability, excellent rate, and low‐temperature performance.